Implementation of Science Learning in Forming Awareness of Environmental Care among Elementary School Students - Listyowati, Enik; Prahani, Binar Kurnia; Gunansyah, Ganes; Hendratno, Hendratno; Istiq'faroh, Nurul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to determine the implementation of science learning in forming the awareness of environmental love among grade V elementary school students at SD N 118 Gresik. The method used in this study is qualitative descriptive with source triangulation through observation and documentation and method triangulation through Focus Group Discussion (FGD), carried out on 20 students and homeroom teachers of grade V of SD Negeri 118 Gresik during science learning. The data analysis method goes through several stages: data reduction, data presentation, conclusion, and data verification. The study results showed that the science learning of the material